Effect of various doses of cinnamon on blood glucose in diabetic individuals - Jadoon, Mahpara Safdar; Alam, Khan; Khattak, Muhammad Muzaffar Ali Khan; Mohammad Siddique, . (Asian Network for Scientific Information, 2004)
The effect of cinnamon doses on blood serum glucose was studied in type 2 diabetic individuals for 60 days. Sixty type 2 diabetic individuals of both sexes and of age 48±6.5 years were divided into 6 groups; each group was having 10 individuals. Groups 1, 2 and 3 were assigned for 1g, 3g and 6g cinnamon doses/day respectively. Groups 4, 5 and 6 were assigned for 1g, 3g and 6g placebo doses/day respectively. The doses were equally distributed over the day. Cinnamon and placebo were given in the form of capsules with breakfast, lunch and dinner. The doses were given for 40 days and after 40 days; there was a 20 days blank period. Fasting blood samples were taken on days 0 (starting day of the experiment) 20, 40 and 60 and blood serums were separated. The blood serum glucose of both the cinnamon and placebo groups were determined. The mean fasting serum glucose levels for cinnamon doses on days 0, 20, 40 and 60 were 208.7, 189.1, 156.5 and 176.6 mg/dl for 1 g cinnamon dose/day; 206.2, 178.4, 170.3 and 177.8 mg/dl for 3g cinnamon dose/day and 233.9, 183.2, 166.4 and 205.7 mg/dl for 6 g cinnamon dose/day respectively. The cinnamon doses significantly (P<0.05) reduced the mean fasting serum glucose levels while the placebo doses did not affect the serum glucose levels. In the light of this research, it is recommended that Type 2 diabetic individuals should use 1-3g cinnamon in their food preparations on regular basis. They can use cinnamon shakers for sprinkling of cinnamon powder on the curry in the plate. They can prepare cinnamon tea without sugar and can use it after meals. Also they can chew cinnamon bark after meals. This will keep their sugar level near to normal values.